Strategies for Shaping Students' Personality in the Islamic Religious Education Process at SMA Negeri 1 Krueng Sabee, Aceh Jaya Regency - Fauzi (Lembaga KITA, 2023)
Islamic Religious Education is a vital aspect of human life that must be prioritized, as happiness and tranquility are achieved through religious adherence and the earnest practice of its teachings. This stems from the religion's inherent emphasis on kindness towards its adherents and its regulation of the conduct of relationships with Allah SWT and the surrounding environment. Islamic Religious Education serves as a pivotal academic discipline aimed at shaping the personalities of students. The effectiveness of this endeavor is contingent upon the strategies employed by educators within this field, and notably, the personality of the educators themselves significantly influences the students' character development. In this thesis, the author employs a descriptive research method, providing a problem-solving approach relevant to contemporary issues associated with the thesis topic. Additionally, a comprehensive library research method is undertaken, involving the examination of a plethora of literature within the library that is relevant to the discussed issues. Based on the research findings obtained in the field, the success of molding students' personalities in the teaching and learning process of Islamic Religious Education is inherently linked to the strategies employed by educators in this field, encompassing the steadfast application of approaches, procedures, steps, and methods in shaping students' personalities. Conclusively, this research contributes valuable insights, drawing several conclusions and recommendations based on the comprehensive discussions presented in the preceding chapters, which are considered beneficial and pertinent to the overall discourse.